KAJIAN LITERATUR MENGENAI HUBUNGAN PENDIDIKAN JASMANI DENGAN KESEHATAN MENTAL PESERTA DIDIK - Ely Yuliawan; Lili Kartika; Devi Yuliani; Della Amanda Sari Sihombing; Rendi Dwi Febrianto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to examine the relationship between physical education and students’ mental health through a literature review of ten national journals published between 2020 and 2025. The analysis summarizes findings related to the role of physical activity, social interaction, and instructional processes in supporting students’ psychological well-being. The results indicate that physical education contributes significantly to reducing stress levels, improving mood, and enhancing self-confidence and social skills. Although several studies report statistically insignificant effects, the overall literature consistently highlights the strategic importance of physical education in promoting mental health, particularly when implemented through effective and developmentally appropriate pedagogical approaches. These findings emphasize the vital role of physical education as a holistic instrument supporting both physical and mental development among students.